1995
DOI: 10.1227/00006123-199510000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Early Treatment of Ruptured Aneurysms with Guglielmi Detachable Coils

Abstract: The major causes of mortality and morbidity in patients surviving the rupture of a saccular aneurysm are subsequent bleeding and vasospasm. The purpose of this study was to evaluate the influence of early treatment of ruptured aneurysms with Guglielmi detachable coils on the incidence of subsequent bleeding. Thirteen patients were treated within 72 hours of initial aneurysm rupture with Guglielmi detachable coils. Excluding three patients who died 2, 4, and 12 weeks after initial hemorrhage, all others have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(33 citation statements)
references
References 23 publications
1
31
0
1
Order By: Relevance
“…Coils placed in the inflow zone block the impact exerted by the blood stream on the aneurysmal wall and induce thrombosis formation within the dome. 9,15 After endovascular treatment, the water hammer effect of the blood flow results in coil compaction in the inflow zone and recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…Coils placed in the inflow zone block the impact exerted by the blood stream on the aneurysmal wall and induce thrombosis formation within the dome. 9,15 After endovascular treatment, the water hammer effect of the blood flow results in coil compaction in the inflow zone and recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] However, incomplete embolization, aneurysm recanalization, and coil compaction remain commonplace. 6,7 The angiographic outcome after coil embolization in small aneurysms is superior to that of large and giant aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Although endovascular treatment of intracranial aneurysms has been widely used because of its efficacy and safety, [1][2][3]5 long-term follow-up studies have shown that aneurysm recanalization and/or regrowth remains a substantial problem, especially for large and giant aneurysms. 2,3,6 Difference in histologic healing between small and large aneurysms may enhance our understanding of aneurysm healing, but no such histologic data have yet been published.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent early rebleeding, increased risk of surgical complications, and the infliction of further damage to the already edematous brain caused by retraction and manipulation of cerebral vessels, endovascular treatment of aneurysms in poor clinical grade after SAH that have anatomically propitious vascular configurations is being increasingly reported [3,7,8,13,22,[30][31][32][33]. The theoretical advantage of the endovascular approach is that it allows early intervention and thus protection from rebleeding.…”
Section: Discussionmentioning
confidence: 99%